IMPLEMENTASI NILAI-NILAI HAM TENTANG KEBEBASAN BERAGAMA DALAM PENETAPAN FATWA MUI TENTANG PERKAWINAN BEDA AGAMA - Nurkafidz Nizam Fahmi (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
This study found that the fatwas of the Indonesian Ulema Council on interfaith marriages were based on two arguments that cannot be separated from one another. The first argument is an Islamic legal argument in the form of the Qur'an, hadith, and ijma> 'based on the interpretation and opinion of the classical authoritative scholars. The second argument is the argument for human rights in the form of religious freedom. Every individual who carries out a marriage that is not in accordance with the Qur'an, Hadith, and ijma> ', is automatically considered to be limiting in terms of religious freedom.They explained that the fatwa was the mechanism of the MUI to bring to orthodox (Sunni) religious understanding. The determination of MUI towards Sunni theology has the consequence of disqualifying other theological concepts. Therefore, the fatwa of the MUI in this field of theology tends to be exclusive. This study also agrees with M.B. Hooker (2003) explained that the MUI fatwas concerning religious freedom were the object of the government's interest in maintaining the integrity of the country. The standard of religious freedom in this context is a standard constructed by the government itself. This study rejects the opinion of Piers Gillespie (2007) who states that the main basis of the publication of the MUI fatwa on interfaith marriage is social factors, not religious or political factors. This factor is the dissatisfaction of the MUI towards the Reformation era (1998-present) which provides broad freedom, especially in freedom of expression.This research is a library research. The approach used is the normative approach of human rights. The primary data of this research is the result of the MUI fatwa collection on religious marriage in 1980-2005. While the secondary sources are the books of Jurisprudence and ushul jurisprudence, which are mainly the MUI reference in fasting, as well as national and international laws on human rights.